Tekstur Tanah dan Respons Tanaman Tanaman Tomat pada Lahan Masam Diaplikasi Asam Humat dari Sari Kulit Buah Kakao - Rahim, Iradhatullah; Maharani, M; Harsani, H; Suherman, S (Journal Galung Tropika, 2021)
Acidic land is underutilized as agricultural land because of its lack of nutrients and minimal water content. At the same time, acid land is widespread in Indonesia. This study aimed to determine the soil texture and response of tomato plants after applying manure and humic acid from cocoa pod extract. Humic acid was extracted from cocoa pod skin compost using the Tan method, while soil texture was measured using the pipette method. The experimental design used was a randomized block design with 3 treatments of giving organic matter to acid soil, including untreated acid soil, acid soil + manure, and acid soil + manure + humic acid. The results showed that acid soil + manure treatment could reduce the sand fraction up to 53%. In addition, there was an increase in values for all growth and production parameters of tomato plants, including plant height, number of leaves, and tomato fruit weight in acid soil. The addition of manure + humic acid to acid soil can also increase tomato plants' wet weight, dry weight, and root volume.